Do hydroelectric projects affect aquatic plants? The case of Marathrum foeniculaceum (Podostemaceae) in two rivers, Southeastern Costa Rica (UNED Research Journal, 2017)
In recent years, natural phenomena have increasingly generated strong and untimely changes in river flow (e.g. the increasingly frequent El Niño and La Niña), but hydroelectric projects are among the main anthropic factors. One potentially affected organism is the plant Marathrum foeniculaceum. To evaluate the potential effects of anomalous change, I simulated the changes in flow through changes in rock position (emerged and submerged) in the Unión River and Convento River, Costa Rica. I studied the phenological behavior of 1 260 individuals in six rocks per river in three replicates (2013, 2014 and 2015). There is evidence of a decrease in flowering duration with respect to natural conditions, due to the correlation between moisture change, wilt progression, phenophase progression and flowering. Fruiting took longer, with no correlation with environmental parameters. On average, the duration from the floral buds to the opening of the fruits was of 20 days, whereas naturally it can extend for several months of the dry season. The average number of flowers per individual was less than two, while in natural conditions it is usually greater than five. Reproductive success was less than 30%; About 60% less than under natural conditions. The frequent changes of flow involved the death of the plants in less than 13 days. Because the reproductive period is seasonal, these flow changes during the rest of the year would cause the plants to die without leaving offspring (seeds), demonstrating one of the adverse and under-estimated effects of hydroelectric projects on aquatic ecosystems.
Keywords: Phenology; hydroelectric project; water; General Valley; Convento River; Union River